Overexpression of the proteasome subunits LMP2, LMP7, and MECL-1, but not PA28 alpha/beta, enhances the presentation of an immunodominant lymphocytic choriomeningitis virus T cell epitope - Schwarz, Katrin; Van den Broek, Maries; Kostka, Susanne; Kraft, Regine; Soza, Andrea; Schmidtke, Gunter; Klötzel, Peter; Groettrup, Marcus (My University, 2000)
The proteasome is a large protease complex that generates most of the peptide ligands of MHC class I molecules either in their final form or in the form of N-terminally extended precursors. Upon the stimulation of cells with IFN-gamma, three constitutively expressed subunits of the 20S proteasome are replaced by the inducible subunits LMP2 (low-molecular mass polypeptide 2), LMP7, and MECL-1 (multicatalytic endopeptidase complex-like-1) to form so-called immunoproteasomes. We show in this study that overexpression of these three subunits in triple transfectants led to a marked enhancement in the H-2Ld-restricted presentation of the immunodominant nonameric epitope NP118, which is derived from the nucleoprotein (NP) of lymphocytic choriomeningitis virus. Overexpression of the alpha and beta subunits of the IFN-gamma-inducible proteasome regulator PA28, in contrast, did not have a comparable effect. In vitro, immunoproteasomes as compared with constitutive proteasomes generated higher amounts of 11- and 12-mer fragments containing the NP118 epitope. These are likely to be cytosolic precursors of NP118, as a proline anchor residue in the second position of NP118 may interfere with TAP-mediated transport of the nonameric epitope itself. In conclusion, we provide evidence that up-regulation of the three inducible subunits, LMP2, LMP7, and MECL-1, can result in a marked improvement of Ag presentation and that, depending on the epitope, PA28 and immunoproteasomes may differentially affect Ag processing.
Keywords: 570